THE EFFECT OF SELF EFFICACY AND SOCIAL SUPPORT ON ACADEMIC ADJUSTMENT WITH ACADEMIC RESILIENCE AS A MEDIATOR - Zulafa Fatharani; Gazi (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to determine the effect of students' self-efficacy and social support on their academic adjustment with academic resilience as a mediator. The sample in this study were 157 students of SMK Triguna Utama from a population of 262 students. The sampling technique used was non-probability sampling with convenience sampling. The measuring instruments used in this study were the Academic Adjustment Scale (AAL), General Self-Efficacy Scale (GSES), Multidimensional Scale of Perceived Social Support (MSPSS), and Academic Resilience Scale-30 (ARS-30). Data analysis used was the result of Path Analysis analysis using the Mplus 7.0 application. The results of the analysis revealed that there was a significant influence of self- efficacy and social support on academic adjustment through academic resilience as a mediator. Self-efficacy and social support influenced academic adjustment. Self-efficacy influenced academic resilience but social support did not influence academic resilience. Academic resilience, social support, and self-efficacy all significantly influence academic adjustment, with social support having the greatest impact. The authors hope that the results of this study can be developed and expanded to include other variables that may influence academic adjustment.